Gaudii: An Automated Graphic Design Expert System - Glez-Morcillo, Carlos; Martin, Victor; Vallejo Fernandez, David; Castro-Schez, Jose; Albusac, Javier (Proceedings of the AAAI Conference on Artificial Intelligence, 2010)
Graphic design is the process of creating graphics to meet specific commercial needs based on knowledge of layout principles and esthetic concepts. This is usually an iterative trial and error process which requires a lot of time even for expert designers. This expert knowledge can be modelled, represented and used by a computer to perform design activities. This paper describes a novel approach named Gaudii (standing for "Intelligent Automated Graphic Design Generator") which utilizes principles and techniques known from the fields of Evolutionary Computation and Fuzzy Logic to automatically obtain design elements. Experimental results that demonstrate the potential of the proposed approach are presented in the area of poster design.